Better arthritis care: What training do community‐based health professionals need to improve their care of people with arthritis? A Delphi study. (26th July 2017) - Erwin, J.; Edwards, K.; Woolf, A.; Whitcombe, S.; Kilty, S.
Abstract: Objective: The aim of the present study was to identify the competencies that non‐specialist community‐based nurses and allied health professionals (AHPs) need to enable them to assess, care for and manage arthritis appropriately. Methods: A Delphi survey with an expert panel of 43 rheumatology specialists and expert patients was used to identify the competencies needed by community‐based nurses and AHPs to enable them to improve their care of people with arthritis. The process was informed by feedback from focus groups with arthritis patients, community‐based nurses and AHPs. Results: The core competencies in arthritis care needed by non‐specialist community‐based nurses and AHPs were identified. The key goals identified were to increase the understanding of arthritis and its impact on patients' lives, and to increase the ability to help patients to self‐manage their condition and access support. Competencies included an understanding of the pathology underlying inflammatory and non‐inflammatory arthritis, the ability to distinguish between the two and the ability to recognize early warning signs, with an emphasis on osteoarthritis (OA), rheumatoid arthritis, gout and septic arthritis. Essential competencies included the ability to engage in shared decision making, goal setting and signposting, to provide patients with education and information and to make appropriate referrals. Conclusions: Health professionals working in the community commonly encounter arthritis as a presenting problem or as a co‐morbidity. The quality of care provided to people with inflammatory arthritis and OA in the community is currently variable. The present study identified the core competencies that all community‐based nurses and AHPs should have in relation to OA and inflammatory arthritis.